Penerapan Metode Mind Mapping pada Pembelajaran Analisis Unsur-unsur Teks Berita - Hastuti Hastuti (LPPM STKIP PGRI Bandar Lampung, 2023)
The learning method is the method used in learning. This method is used to achieve competence in the material given to students at that time. The use of this learning method has of course been adapted to the needs of students and teachers as well as the suitability of the material. This type of research is descriptive qualitative with data collection techniques are measurement techniques. Measurements were made to measure students' ability to analyze news elements. The results of the study show that the application of the Mind Mapping method to learning to analyze news elements has benefits and constraints in its application. The final results obtained from the application of the Mind Mapping method are said to be good, from the calculation results the average value is 75.8..